Antimonun ateşte rafinasyonunda demir ve arseniğin davranışı - Açma, Ercan (Fen Bilimleri Enstitüsü, 1988)
Bu çalışmada; demir ve arseniğin sodyumlu flakslar ve oksitle yici veya sülfürleyici maddeler ilavesiyle ham antimondan ateşte rafi nasyon yoluyla giderilmesi teorik ve deneysel olarak incelenmiştir. Yapılan kaynak araştırmalarına göre kavurma-redüksiyon yöntemiyle üre tilen ham antimon, raf inasyonu gerektirecek konsantrasyonlarda demir ve arsenik içermektedir. Bu empüriteler sadece ateşte rafinasyonla gider ilebilmektedir. Ateşte rafinasyon sırasında antimon kayıplarının önlenmesi için düşük ergime sıcaklğına, akışkanlığına ve örtücülük ö- zelliğine sahip mat ve cürufların oluşturması şarttır. Bu özellikleri Na2C03, NaCl, NaOH ve Na2SC>4.10H20 gibi sodyumlu tuzlarla sağlanmakta dır. Rafine edici madde olarak SD2S3, NaNC>3 ve havanın kullanımı yay gındır. Yapılan deneylerde yapay Sb-Fe ve Sb-As alaşımları ile ve or jinal ham antimon numuneleri kullanılmıştır. Yapay alaşımlarla ger çekleştirilen deneylerde en az antimon kaybıyla en etkin demir ve ar senik arıtımını sağlayacak sıcaklık, süre, rafine edici madde türü ve miktarı ile f laks tür ve miktarları saptanmıştır. Deneysel olarak tespit edilen bazı önemli sonuçlar aşağıdadır. 1) Uygun sıcaklıklar demir için 900, arsenik için 950°C'tur. 2) Yeterli rafinasyon süreleri demir için Sb2&3 ve NaNÛ3 ilavesinde 4 saat, havayla oksidasyonda 2 saat, arsenik için 2 saattir. 3) Rafinasyon için antimondaki 1 kısım demire 2 kısım Sb2S3, 2 kısım NaNÛ3 ilavesi ve 1 kısım arseniğe 3 kısım NaNÛ3 ilavesi yeterli dir. Optimal hava miktarı 300 mi hava/dak. kg Sb'dur. 4) En düşük empürite konsantrasyonu ve antimon kaybıyla raf inasyonu mümkün kılan flaks karışımları demir için sülfürieyici şartlarda 25 Na2C03 + %10 NaCl, oksitleyici şartlarda %10 Na2C03 + %40 NaCl ve arsenik için %20 Na2C03 + %15 NaOH + %5 NaCl'dür. 5) Deneylerde rafine edilen antimondaki demiri sülfürleyerek %0.020 Fe; oksitleyerek %0.005 Fe; arseniği ise %00015 As değerlerine kadar indirmek mümkündür. 6) %97.9l Sb içeren orjinal bir ham metali, havayla oksitleyerek, %95 antimon verimiyle, %99.915 Sb tenörüne kadar saflaştırmak müm kün olmaktadır. 7) Optimal şartlarda yapılacak antimon rafinasyon işlemleri sadece Türkiye için yılda 256 ton regulus tasarrufu yaratabilecektir. Bu tasarrufun maddi tutarı günümüz fiyatlarıyla 560 milyon TL.- etmektedir

In the present work the removal of iron and arsenic by fire refining from crude antimony produced by roasting-reduction process is investigated. The theoritical studies are covered as follows: - Kinds and concentration of empurity elements in crude antimony - Relationship between empurity cocentrations and production process of antimony - The chemical forms of the empurities which are present in crude antimony - The reactions between slag or matte phase and metal phase during fire refining The antimony, in general, is produced from its sulphur ores by p'yrometal- lurgical processes. "These pyrometallurgical processes are: ' - Roasting-Reaction process - Precipitation process - Roasting-Reduction process But, roasting-reduction process is preferred for industrial application. At the roasting step of this process, antimony as an oxide (Sb2Û3) is collected in the flue dust contaning iron and arsenic as empurities. Therefore the crude antimony have to be refined after reduction in order to decrease iron and arsenic concentration to acceptable levels. In crude antimony; iron is as FeSb2 form (inter- metalib compound) and arsenic is as Sb.As form (mixed crystal). In the industrial applications, iron and arsenic are removed by fire refining operations. Iron is removed from crude antimony by sulphurizing with Sb2So and by oxidizing with NaNÛ3 or air. However removal of arsenic from antimony is required by adding alkali flux in oxidizing conditions. Matte ve slag phases are formed in order to prevent volatilization losses and to collect empurities in the compounds during refining. The desirable properties of these phases are: vi - low smelting temperature - low viscosity - high covering ability The fluxes which contained sodium are added to the crude antimony to obtain matte and slag phases. In industrial applications of crude antimony refining soda ash (Na2C03>, salt (NaCl), caustic soda (NaOH) and glober salt (N^SO^.IO^O) are generally used. The experimental works for removal of iron and arsenic by fire refining from crude antimony were carried out. on synthetic Sb-Fe and Sb-As systems and original crude antimony samples. The experimental conditions providing minimum iron and arsenic concentrations in antimony with a maximum antimony eff icency during fire refining are investigated using synthetic alloys. The experimental parameters investigated are: - Optimal refining temperature - Optimal refining time - Kind of refining agent - Amount of refining agent - Kind of flux - Amount of flux Then, the original crude antimony samples are refined under optimum conditions which are determined for synthetic alloys of Sb-Fe and Sb-As. Synthetic alloys consist of iron and arsenic in range of 1% to 3%. These alloys are produced from the commercial refined antimony, iron powder (Merck) and As203 (Merck). The original crude antimony contains 97.91% Sb, 1.63% As and 0.28% Fe. The experiments are carried out in Tammann furnace which can be heated to 2000°C under reducing atmosphere. Reducing atmosphere in this furnace is due to carbon heating element. The samples are smelted in the alsint crucibles. The refining temperature is investigated in range between 800 and 1100°C, refining time from 0.5 to 6 hours. Na2C03, NaOH, NaCl and Na2SO4, 10H2O (Merck) are used as a flux during fire refining. The refining agents Sb2S3 (Merck), NaN03 (Merck) and air are also employed. vxx Temperature was measured with a Pt-Pt 10 Rh termpcuple during refining experiments. The furnace temperature was maintained with ± 10°C sensivity., The antimony samples were taken from the inside of the alsint crucible by puar and silica tube during experiments at various the refining time. The chemical analysis of antimony, slag and matte samples were carried out by an atomic absorptionspectrometer and a spectrofotometer. Sometimes chemical analysis were carried out by wet methods top. Form of compounds present in the matte and slagcphases were identified by X-Ray analysis after recrystalization of the matte and slag phases for 24 hours at 500°C. The important experimental results obtained from removal of iron and arsenic by fire refining from antimony are as follows: 1) The optimum removal temperature is 900°C and 950°C for iron an arsenic respectively during refining of antimony. As long as the refining temperature exceeds 900 or 950°C, the empurity concentrations of rafined antimony increases. 2) Four hours is found to be enough time for removing of iron from antimony with adding Sb2S3 and NaN03 under all experimental temperatures. Iron can be removed from antimony for 2 hours by using air as an oxidizing agent arsenic can be decreased to desirable concentration in antimony by oxidizing either with NaN03 or air after 2 hours under all experimental temperature. 3) Optimum amounts of refining agent are found from the fire refining experiments on the synthetic Sb-Fe and Sb-As alloys as follows: - for one unit of iron in antimony; two units Sb2S3 - for one unit of iron in antimony; two units NaNÛ3 - for one unit of arsenic in antimony; three units NaN0~ Blowing of "300 ml air/min. kg Sb" into antimony bath as an oxidizition agent is. found to be enough for iron and arsenic refining from antimony;.Adding of Sb2S3 more than mentioned above causes increasing of sulphur concentration in antimony. When the air flow is exceeded "300 ml air/min. kg Sb" vapor izitation- losses of antimony is increased. 4) In order to refine antimony stibnite concentrate can be used by sulphurization of -iron in antimony instead of Sb2S3» However arsenic and lead present in the stibnite concentrate should be lower so that it does'nt contaminate the refined antimony. The iron ) dissolved in crude antimony as FeS from can be removed only by Na2S obtaining by reduction of glober salt with coal. viii 5) Obtaning of minimum arsenic and iron concentration level in the refined antimony with maximum antimony efficiency is possible by using flux combinations which are given belowj - removal of iron from antimony by sulphurization: 5% Na2C03 * 10% NaCl - removal of iron from antimony by oxidation: 10% Na2C03 * 40% NaCl - removal of arsenic from antimony by oxidation: 20% Na2C03 +15% NaOH * 5% NaCl 6) Iron goes into the matte phase and. slag phase, arsenic goes into the slag phase which form same compounds during fire refining of antimony. This result can be expressed as Log % Fe Sb - Log LTe, Log % Fe sb - Log LFe and Log % As sb - Log L^m relations. Different empurity concentrations in the matte and slag phases are resulted from the varition pyhsical properties of the matte and slag phases with adding fluxes containing sodium. 7) Under optimum experimental conditions, iron and arsenic concentra tion in antimony can be reduced fairly small percentages which are given below: 0.020% Fe by adding Sb2S" 0.010% Fe by adding NaN03 0.005% Fe by blowing air 0.10% As by adding NaN03 0.015% As by blowing air. The avarage antimony efficiency is 95% under optimum refining conditions. 8) The original crude antimony are observed to be produced by roasting-reduction process has been rafined for 2 hours at 950°C while blowing 300 ml air/min. kg Sb and adding mixed flux (%20 Na2C03 + %15 NaOH + %5 NaCl). The chemical composition of the crude antimony is as follows: IX 97.91% Sb 0.28 % Fe 1.63 % As 0,02 % Cu 0.07 % Pb 0,09 % S The antimony efficiency was found to be. approximately 95% at the end of fire refining. The chemical composition of rafined antimony is as follows: 99.915 % Sb 0.006 % Fe 0.009 % As 0.013 % Cu 0.034 % Pb 0.023 % S The chemical composition of the metal can meet the values put by ASTM B 237-52 standart.. 9) The cheapest flux is Na2CX>3 and the cheapest refining agent is air for the desired iron and arsenic concentrations is refined antimony. Na2CÜ3 can product by burning of commercial sodastone (Na2C03.7H20). The arsenic concentration in crude antimony from 1.0% to 0.05% and the iron concentration in crude antimony from 1.0% to 0.005% can be decreased only by blowing of air and by adding of Na2C03 under optimum refining temperatures (900°C and 950°C) and under optimum refining time (2 hours). 10) The antimony efficiency is about 90% in technical refining appli cations. The antimony efficiency could be increased to 95% if the refining operations are done under the optimum conditions suggested in this study. The saving provides 256 ton refined antimony per year to Turkey and it's equal to 56x10' TL.
Behavior of iron and arsenic during fire-refining of antimony
Tez (Doktora)-- İTÜ Fen Bil. Enst., 1988.
Keywords: Antimon; Arsenik; Demir; Rafinasyon; Antimony; Arsenic; Iron; Refining